PERANCANGAN MODEL SISTEM PENGATURAN LALU-LINTAS KENDARAAN YANG AKAN MEMOTONG TITIK PUTAR-BALIK PADA JALUR BUSWAY - Hadian S.U, Hadian S.U; Hugeng, Hugeng; Sanjaya, Andy (TESLA Jurnal Teknik Elektro UNTAR, 2007)
The design of traffic light management system for vehicle which will turn around, by placing the censors to detect the Transjakarta bus. The traffic light will indicated if Transjakarta bus get near the turn around point.